Deíxis frente a anáfora en griego antiguo (Minerva. Revista de Filología Clásica, 2019)
The fact that the distinction between deictics and anaphor (i. e. between actual mostration and linguistic correferentiality) is reflected on the grammatical level in Old Greek allows us to account for the system of personal and demonstrative pronouns and the use of spatial and temporal expressions in this language.